An Integrative Review of HR Analytics Implementation - Kebiat Mukuze; Desderio Chavunduka; Faitira Manuere; Pilot Ndhlovu (African Journals on line (AJOL), 2023)
Different organizations worldwide are increasingly turning to human resource analytics to improve their strategic human resource and business goals. Specifically, this has been necessitated by advances in information technology in the corporate business world. Therefore, this advancement in information technology has heightened expectations and contributed to a positive perception of human resource analytics. On the other hand, using HRA to manage the human endeavor is still marred by different implementation challenges owing to a lack of understanding and appreciation by the key stakeholders. Using an integrative synthesis, the researchers conducted an integrative review of refereed journal articles on HRA Implementation. A search from three major data banks turned up 133 410 hits, and according to the search criteria, only twelve relevant articles were reviewed. Consequently, the number of articles in refereed journals and the research question addressed were used to categorize the articles. The articles were classified according to the following four questions: What exactly is HRA? How does HRA function? What are the consequences of using HRA? What factors influence HRA adoption? Researchers concluded that despite information connecting HRA adoption to firm strategic performance, academic research and HRA adoption are extremely low, resulting in a scarcity of evidence on the subject. All in all, such a revelation warrants further investigation through longitudinal and cross-sectional field surveys.